IMPROVING STRUCTURAL INTEGRITY OF WIND TURBINE IN EXTREME CONDITIONS WITH THE HELP OF TELECOM NETWORKS - Felix Răduică, PhD Student; Ionel Simion, PhD (Journal of Industrial Design and Engineering Graphics, 2017)
This paper describes a method of improving the life span of a wind turbine and optimizing its structural integrity by applying networking and telecommunication monitoring and real-time computation for an enhanced turbine design. The authors try to accomplish the goal of extending the lifespan of a wind turbine by applying networking equipment to provide real-time data and to establish decision making with the help of the computer results of data analysis and simulation.